2019
DOI: 10.21608/zumj.2019.23700
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Serum Interleukin-18 in Hepatitis C Patients in Zagazig University Hospitals

Abstract: Background: HCV is a contagious blood-borne virus that attacks the liver and can be deadly despite often having no visible health warnings. IL-18 is an important proinflammatory cytokine secreted from Kupffer cells. It is involved in the pathogenesis of HCV infection through modulating immune functions by regulating IFN-γ production and promoting the development of Th1 immune responses. Objective: The aim of this study is to measure serum level of Il-18 in chronic hepatitis C patients and compare between Il-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…However, El-Amin et al observed that serum IL-18 is markedly elevated and is associated with TE-staged liver fibrosis. Therefore, in individuals with chronic hepatitis C, IL-18 can be employed as a noninvasive proinflammatory marker to assess the severity and chronicity of liver fibrosis [22]. Equally, Selim et al and Said et al found that there was a statistically significant direct link between IL-18 plasma level and the severity of liver disease as measured by METAVIR necro-inflammatory grade (A) and fibrosis stage (F) [10,23].…”
Section: Validity Of Il-18 Pg/ml Level As a Diagnostic Marker For Ev ...mentioning
confidence: 99%
“…However, El-Amin et al observed that serum IL-18 is markedly elevated and is associated with TE-staged liver fibrosis. Therefore, in individuals with chronic hepatitis C, IL-18 can be employed as a noninvasive proinflammatory marker to assess the severity and chronicity of liver fibrosis [22]. Equally, Selim et al and Said et al found that there was a statistically significant direct link between IL-18 plasma level and the severity of liver disease as measured by METAVIR necro-inflammatory grade (A) and fibrosis stage (F) [10,23].…”
Section: Validity Of Il-18 Pg/ml Level As a Diagnostic Marker For Ev ...mentioning
confidence: 99%